DETERMINAN METODE PEMBAYARAN AKUISISI DI INDONESIA: BUKTI EMPIRIS DI INDONESIA - Rahmat Setiawan; Valiant Nur Hasyim (UNUSA Press, 2019)
This research purpose to examine what factor that determine method of payment acquisition in Indonesia. The period of sample during 2000-2017 and using multinomial logistic regression. There are 85 samples of transanctions (57 using cash payment, 18 using mix payment, and 10 using stock payment). Independent variables are market to book ratio, market capitalization, tobin’s Q, cash flow, and standard deviations of return. Acquirer Correlation as a control variable. This study find that market to book ratio has positive effect on stock and mix payment method than cash payment method at 10%. Tobin’s Q has positive effect on mix payment method than cash payment method at 10%.